The effect of Maras powder and smoking on the microRNA deregulation of oral mucosa (Journal of Applied Oral Science, 2021)
Objective: This study aimed to investigate the effects of Maras powder (a type of smokeless tobacco obtained from Nicotiana rustica Linn and mixed with the ashes of wood, especially from oak, walnut or grapevine) on the microRNA (miRNA) deregulation of oral mucosa, and it compares these effects with those of smoking. Methodology: Oral mucosal samples were collected from 74 patients, consisting of 16 nonusers, 26 smokers, and 32 Maras powder users. Genes associated with oral cancer were selected and 90 microRNAs targeting these genes were identified. MicroRNA were isolated and purified using the microRNA isolation kit. MicroRNA were expressed using Fluidigm RT-PCR. Results: A positive correlation between the duration of Maras powder use with miR-31 expression levels, and a negative correlation between the Maras powder chewing time and miR-372 expression levels was found. In addition, there is a negative correlation between the amount of Maras powder consumed and expression levels of miR-375, miR-378a, miR-145, and miR-10b; moreover, another negative correlation is observed between the number of cigarettes consumed and the expression levels of miR-23a, miR-23b, miR-203a, miR-200b, and miR-375. However, miR-200b and miR-92a levels were downregulated significantly more in Maras powder users when compared with smokers and nonusers (p<0.05). Conclusion: The results show both chewing Maras powder and smoking have an effect on deregulation of miR-200b and miR-92a expressions. This leads to the belief that assessing the expression of these two miRNAs is a promising noninvasive method of analysis, especially in mutagen exposures. Finally, large-scale and high-throughput studies may help to identify an extensive miRNA expression profile associated with tobacco use and improve the understanding of oral malignancies.